Sunni jurisprudent’s view on the father’s Walayat in marriage of virgin girl - M. Mousavi Bojnourdi, M.A. Sarfi, (Opción, 2019)
The article aims to investigate the issue of father’s walayat (guardianship) on the marriage of the virgin mature daughter by quantitative research methods like reviewing the jurisprudential and historical views of Imamiya and Sunni jurists. As a result, despite the consensus on the walayat of the father or paternal grandfather on the minor virgin, there are contradictory views on the walayat of the father or paternal grandfather on mature virgin. As a conclusion, the civil law has deemed it necessary to obtain wali’s permission due to social security issues and the protection of the rights of girls in the society.